Unicorn Rescue Society : The Creature of The Pines - Gidwitz, Adam; Hatem Aly (United States Dutton Children's Books, 2018)
A middle-grade series following students Elliot Eisner and Uchenna Devereaux, who join their eccentric teacher, Professor Fauna, to protect endangered mythical creatures.
The Creature of the Pines (2018), The Basque Dragon (2018), Sasquatch and the Muckleshoot (2018), The Chupacabras of the Rio Grande (2019), The Madre de Aguas of Cuba (2019/2020), and The Secret of the Himalayas (2022)
English
Keywords: friendship; environmental conservation; adventure